(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
On November 8, 2016 evening an economic surgical strike like decision of Prime Minister Mr. Narendra Modi hit the nation of withdrawing the 1000 and 500 rupee bills with immediate effect from 12.00 of mid night and time bound surrender of the said notes in circulation. The demonetization decision of the NDA Government brought a hue and cry from many including political parties, economists, policy makers, development agencies, civic societies and individuals among others. In his address to nation, Prime Minister Mr Modi strongly advocated in favour of the decision for the betterment of the nation. Initially, demonetization caused many hardships to the people of this largest economy living in cash economy; however it would have positive impact in the long run. People across professions and status have extended their support of the Government with a hope that demonetization would be an effective in combating corruption, promoting transparency in business practices, and hammering on the shadow economy and black money. Moreover, the digital programme under financial inclusion will get a big boost in promoting direct transfer of benefits of Government sponsored schemes to poor. However, there are many challenges in making this big Indian cash economy to cash less digital market. In these backdrops, the exiting paper will discuss the opportunities and challenges of demonetization.